2019
DOI: 10.1038/s41418-019-0410-x
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor signal strength and epigenetic control of Bim predict memory CD8+ T-cell fate

Abstract: Most effector CD8+ T cells die, while some persist and become either “effector” (TEM) or “central” (TCM) memory T cells. Paradoxically, effector CD8+ T cells with greater memory potential have higher levels of the pro-apoptotic molecule Bim. Here, we report, using a novel Bim-mCherry knock-in mouse, that cells with high levels of Bim preferentially develop into TCM cells. Bim levels remained stable and were regulated by DNA methylation at the Bim promoter. Notably, high levels of Bcl-2 were required for Bimhi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Importantly, enrichment of TCR‐related genes TRAV30 and NR4A1 (Nur77) was also detected. Nur77 is known to indicate T‐cell receptor signaling strength and is associated with memory cell development (Li et al , 2020 ; Shin et al , 2020 ). Notably, Nur77 has recently been identified as a central regulator of T‐cell immunometabolism (Liebmann et al , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, enrichment of TCR‐related genes TRAV30 and NR4A1 (Nur77) was also detected. Nur77 is known to indicate T‐cell receptor signaling strength and is associated with memory cell development (Li et al , 2020 ; Shin et al , 2020 ). Notably, Nur77 has recently been identified as a central regulator of T‐cell immunometabolism (Liebmann et al , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although strong TCR stimulation is typically identified with terminal T cell differentiation ( 30 ), a recent study demonstrated that greater TCR stimulation can favor T CM differentiation when coupled to high levels of Bim and Bcl2 ( 31 ), which would not be dependent on differences in viral loads. However, it is also possible that PSGL-1-deficiency allows for greater activation of SLECs due to more limited PD-1 expression, thereby driving their terminal differentiation and promoting increased representation of MPECs.…”
Section: Discussionmentioning
confidence: 99%
“…However, another consideration is the speculated roles of EZH2 in TCR signaling supported by evidence of non-nuclear localization ( 57 , 58 ). Although seemingly disparate, EZH2's proposed cytoplasmic involvement in TCR signaling could very well explain the differences in CD8+ T cell differentiation as TCR signal strength is known to influence memory versus effector cell fate ( 46 , 59 ). In the context of cancer, there is chronic antigen stimulation where such phenotypes as SLEC and MPEC may no longer be applicable, making the comparison to acute pathogenic infection more complicated in defining the CD8+ T cell subpopulations affected by EZH2 inhibition.…”
Section: Discussionmentioning
confidence: 99%